Detailed modelling to evaluate the effectiveness of sediment recycling on coastal habitat - Spearman, Jeremy; Benson, Thomas (Frontiers in Earth Science, 2023)
In many parts of the world, ports and harbours lie adjacent to ecologically important areas of coastal habitat. In such areas port authorities, coastal managers and regulators are required to negotiate the tension between the demands of making ports ever more efficient, with wider and deeper approaches to accommodate vessels of deeper draft and larger handling areas, and the preservation of coastal habitats which are vitally important for bird and fish populations and which help protect the coast from flooding and erosion. The deepening of approach channels and berths usually results in an increased rate of sedimentation and maintenance dredging. There is an increasing recognition that such dredged sediment is a resource which should be utilised beneficially for human development activities and/or enhancement of ecological habitats. One form of beneficial use of dredged material, is termed “sediment recycling” or “strategic placement” . This form of beneficial use consists of the placement of cohesive sediment into the water column or onto the bed in such a way so that currents and waves then transport the released sediment onto the desired habitats. Sediment recycling is less widely practiced because the changes in bed level resulting from placement are generally of the order of a few centimetres/year or less and it is difficult to demonstrate whether such recycling is successful. This paper describes a methodology for the assessment of the effectiveness sediment recycling, implementing the methodology on a case study of a large-scale sediment recycling scheme in the Stour/Orwell Estuary system in the UK, designed to offset the identified adverse effects of an approach channel deepening on the estuary system. The study represents a major contribution to the consideration of non-direct beneficial use of cohesive sediment. For the first time a methodology for reliably evaluating the effects of sediment recycling, separating the effects of natural changes in morphology from the beneficial use, has been shown to be effective. This allows a robust evaluation of the effectiveness of such methods and crucially enables these methods to be tested and optimised using modelling before implementation.